DNA interactions, antitubercular and cytotoxic activity of heteroleptic Cu-II complexes containing 1,10-phenanthroline - Almeida, Janaina do Couto; Silva, Raphael T. C.; Zanetti, Renan D. [UNESP]; Moreira, Mariete B. [UNESP]; Portes, Marcelo C.; Polloni, Lorena; Vasconcelos Azevedo, Fernanda V. P. de; Von Poelhsitz, Gustavo; Pivatto, Marcos; Netto, Adelino V. G. [UNESP]; Avila, Veridiana de Melo R.; Manieri, Karyn F. [UNESP]; et al. (Elsevier B.V., 2021)
Herein, we describe the synthesis and characterization of novel heteroleptic copper(II) complexes, [Cu(2-HNA)(phen)ClO4]center dot 1 center dot 5H(2)O I, [Cu(6-HNA)(phen)ClO4]center dot H2O II, [Cu(QNA)(phen)ClO4]center dot 0 center dot 5H(2)O III and [Cu(2-MNA)(phen)ClO4]center dot 0 center dot 5H(2)O IV, where 2-HNA = 2-hydroxynicotinic acid, 6-HNA = 6-hydroxynicotinic acid, QNA = 2-quinolinecarboxylic acid, 2-MNA = 2-mercaptonicotinic acid and phen = 1,10-phenanthroline. The spectral data indicate a square-pyramidal geometry around the copper(II) ion in the solid state, with an acid derivative and 1,10-phenanthroline (N-N) acting as bidentate ligands. A perchlorate ion in the apical position completes the metal coordination sphere. All these complexes exhibited potent activity against the Mycobacterium tuberculosis H37Rv strain, with MIC values in the range of few mu M. The cytotoxic activity of these compounds was also investigated toward tumor cell lines (MDA-MB-231 and MCF-7) and in a non-tumorigenic cell line (MCF-10A). Complex I was the most active (IC50 = 4.2 mu M) and selective (SI > 3) toward MDA-MB-231 cells. DNA binding studies performed by circular dichroism (CD) and UV-Vis spectroscopic methods, using a Hoechst 33258 displacement assay, indicated that these complexes can efficiently bind to ct-DNA, with K-b values in the range of 10(3) M-1. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Copper(II) complexes; Cytotoxic activity; Mycobacterium tuberculosis; DNA binding studies; S[ectroscopic methods